Review Journal Thermodynamics Carbon Active Adsorption Empty Fruit bunch of Heavy Metal from Liquid Waste - Kurnia Sandi; Ricky Andi Syahputra; Moondra Zubir (Indonesian Journal of Chemical Science and Technology (IJCST), 2020)
Research on metal adsorption isotherms with activated carbon oil palm empty fruit bunches in liquid waste. Oil palm empty fruit bunches are used as adsorbent for metal absorption. Oil palm empty fruit bunches are prepared at 105O C for 24 hours to get a constant weight then are characterized by SEM. Oil palm empty fruit bunches are heated at temperatures (400O C – 700O C) to get activated carbon. Re-characterization using SEM at optimum conditions shows that the pore surface is expanding. Then with a batch method for metal absorption (Cu, Pb, Hg) and analyzed using AAS. The most common absorption of activated carbon of oil palm empty fruit bunches is Cu (II). Based on the Langmuir and Freundlich R2 models close to 1, which means that multi-layer adsorption occurs.